2020
DOI: 10.1002/icd.2184
|View full text |Cite
|
Sign up to set email alerts
|

Maternal emotion dysregulation and physiological concordance in mother‐preschooler dyads

Abstract: Maternal emotional and physiological dysregulation has been found to influence child stress physiology. This study characterizes diurnal cortisol and basal heart rate variability (HRV) patterns in a predominately high-risk sample of mothers with a full range of emotion dysregulation and assessed the magnitude of concordance (N = 68 motherpreschooler dyads). Overall, dyads exhibited concordance in evening salivary cortisol levels, but not for morning levels or HRV. Maternal emotion dysregulation was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“… 54 All postpartum assessments include behavioural observations of parenting in a mother–infant/child-free play, 55–57 as well as high-frequency HRV assessed in mothers during a baseline 2 min period when no task is occurring and during the mother–infant/child-free play interactions. 58 59 We use the standard placement on the body for HRV assessment using three leads attached to the upper chest.…”
Section: Methods and Analysismentioning
confidence: 99%
“… 54 All postpartum assessments include behavioural observations of parenting in a mother–infant/child-free play, 55–57 as well as high-frequency HRV assessed in mothers during a baseline 2 min period when no task is occurring and during the mother–infant/child-free play interactions. 58 59 We use the standard placement on the body for HRV assessment using three leads attached to the upper chest.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Researchers have also found that adolescents who display a more normative, steeper decline in diurnal cortisol levels tend to have greater levels of high arousal positive affect, reflected in higher activity levels and alertness (Hoyt et al, 2015). Findings in the literature are somewhat inconsistent with regard to whether morning cortisol levels or diurnal decline are most strongly associated with emotion regulation (Laurent et al, 2013;O'Brien et al, 2020;Zalewski et al, 2012). Articulating the interplay between the social environment, specifically family routines, and emotion-related physiological processes, such as the HPA axis, will allow for better understanding of the environmental factors most important to shaping the development of emotion regulation, specifically affective balance, during early childhood.…”
Section: Introductionmentioning
confidence: 99%